Bevacizumab in hereditary hemorrhagic telangiectasia-associated epistaxis: effectiveness of an injection protocol based on the vascular anatomy of the nose - Dheyauldeen, Sinan; Dollner, Ralph (The laryngoscope, 2012)
Objective/Hypothesis: To evaluate the effectiveness of a standardized intranasal bevacizumab injection in treating hereditary hemorrhagic telangiectasia (HHT)-associated epistaxis. Study Design: Prospective pilot study. Methods: A total dose of 100 mg bevacizumab (25 mg/mL Avastin) was injected submucosally, 50 mg on each side. A total of 0.5 mL was injected in the sphenopalatine area, upper part of bony septum, upper part of the later nasal wall, and the anterior part of nasal floor. No cauterizations or laser therapy were done during or after the procedure. The hemoglobin level and grades of epistaxis were recorded before and monthly after the procedure. The IFT grading system (intensity [I], frequency [F] of epistaxis, and the amount of blood transfusion [T]) and epistaxis severity score (ESS) for hereditary hemorrhagic telangiectasia system were used. Quality of life (QoL) was evaluated before and 4 weeks after the procedure using the Short Form-36 Health Survey questionnaire, Cantril's Self-Anchoring Ladder questionnaire, and Slotosch disease-specific QoL questionnaire. Results: A significant improvement was found in IFT grading (P = .007), ESS grading (P = .001), and hemoglobin level (P = .01). The QoL differences were statistically not significant. Conclusions: The four-injection site technique of intranasal administration of bevacizumab is an effective treatment option in HHT-associated epistaxis, at least on the short-term effect. Long-term and comparative studies are needed to further evaluate the significance of this treatment modality. Laryngoscope, 2012
Gesehen am 11.12.2018